"THE USE OF INNOVATIVE TECHNOLOGIES IN TEACHING PRIMARY SCHOOL" (Conferencea, 2022)
This article shows the effective aspects of the use of innovative methods in primary school, the process of integration between disciplines, the possibilities of information and communication technologies in the creation of innovative methods. The article also recommends “Rainbow Gloss”, “Double Fingers”, and innovative “Crossword” methods.